Understanding cervical cancer, human papillomavirus (HPV), and HPV vaccine acceptance in college-going students: Institutional-based cross-sectional study from Bihar State - Ekta Krishna; Shreyas Kumar Patil; Santosh Kumar Nirala; Bijaya Nanda Naik; Vijay Kumar; Chanda Mani Singh; Vijay Kumar (Journal of Family Medicine and Primary Care)
Background: Cervical cancer is the second leading cause of cancer-related deaths in Indian women, constituting a significant public health problem. Improving knowledge regarding cervical cancer, human papillomavirus (HPV), and HPV vaccines will help in increased vaccine acceptance and prevention of cervical cancer. Material and Methods: This cross-sectional study was conducted among 801 college-going students of Patna, Bihar, using a predesigned, semistructured, self-administered questionnaire. Data analysis was performed using the SPSS version 20 (Statistical Package for Social Sciences) software. Results: A total of 801 students participated in the study, and the mean (SD) age was 20.6 ± 2.2 years. The knowledge of students in the medical group was found to be higher than that in the nonmedical group. In the medical group, 93% of the students were aware of cervical cancer versus 71.3% students in the nonmedical group. Awareness regarding the etiological role of HPV in cervical cancer was 84.3% in the medical group compared to 16% in the nonmedical group. Most (82.5%) medical students knew of the existence of a vaccine against HPV in contrast to just 12.5% of the nonmedical group. Willingness to take the vaccine in the medical group was 84.3% versus 46.5% in the nonmedical group. Willingness to pay for the vaccine was reported by 55.6% and 7.5% in the medical and nonmedical groups, respectively. Conclusion: The comparative results of the two groups identified specific areas where awareness campaigns should be intensified for both medical and nonmedical groups. This study further highlighted nonmedical students, which also represents the general population has very less knowledge about HPV and the HPV vaccine. The findings emphasize the importance of awareness campaigns and educational interventions to improve understanding and vaccine uptake among potential beneficiaries.